Chicken cartilage-based carbon material as well as preparation method and application thereof

By using chicken cartilage to prepare carbon materials, the problem of waste of chicken cartilage resources is solved, high value-added utilization is achieved, and carbon materials with excellent electrochemical properties are prepared, providing a new choice for capacitor electrode materials.

CN119560315APending Publication Date: 2025-03-04CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411733840.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, chicken cartilage has been developed and utilized less in the field of carbon materials, resulting in a large amount of chicken cartilage resources being wasted and its potential high value-added conversion is not achieved.

Method used

Carbon materials with special structure and properties are prepared by pre-carbonization, activation, carbonization and composite polyaniline processes. The method includes steps such as cleaning, drying, crushing, pre-carbonization, soaking in a saturated KOH solution, carbonization, washing and composite polymerization.

Benefits of technology

The high added value utilization of chicken cartilage resources has been achieved, and the prepared carbon materials have excellent electrochemical properties, including high specific capacitance and fast charging and discharging performance, providing a new choice for the development of capacitor electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005160985050000011
    Figure HDA0005160985050000011
  • Figure HDA0005160985050000012
    Figure HDA0005160985050000012
  • Figure HDA0005160985050000021
    Figure HDA0005160985050000021
Patent Text Reader

Abstract

The invention relates to the field of electrode materials, in particular to a chicken cartilage-based carbon material and a preparation method and application thereof. The carbon material is prepared by taking chicken cartilage as a raw material. The preparation method comprises the following steps: (1) cleaning and crushing the chicken cartilage; (2) pre-carbonizing, and then grinding; (3) alkaline leaching; (4) carbonizing and washing; and (5) aniline modification. By improving and optimizing the preparation process of the carbon material, the capacitor prepared from the chicken cartilage-based carbon material has high specific capacitance and good charge-discharge performance, the preparation process is simple, the raw materials are green and environment-friendly, the cost is low, and high value-added utilization of the chicken cartilage which is a cheap and rich resource is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrode materials, and specifically relates to a chicken cartilage-based carbon material and a preparation method and application thereof. Background Art

[0002] Biomaterials always have complex structures and compositions, and are non-toxic, non-polluting, widely available, low-cost, renewable, high in carbon content, and good in biocompatibility. This gives them appropriate natural properties in carbon materials, which cannot be achieved through artificial synthesis. Currently, most bio-based sources are plants and some animal fur. Studies have shown that using biomaterials such as pig bones and cuttlefish bones to make carbon materials can obtain carbon materials with good electrochemical properties.

[0003] Chicken cartilage is a by-product of the chicken processing industry. Chicken cartilage itself has a high carbon content and is rich in organic components such as collagen and chondroitin sulfate, which enables it to provide a rich carbon source when preparing carbon materials, which is conducive to the formation of high-quality carbon materials. However, despite these potential advantages of chicken cartilage, the current methods of using it to prepare carbon materials with good electrochemical properties still need to be explored and improved. At present, the use of chicken cartilage is mostly concentrated in the field of food processing, such as making chicken cartilage snacks, etc. In the field of carbon materials, its development and utilization are relatively small, and a large amount of chicken cartilage resources are wasted, and its potential high added value conversion has not been realized. Summary of the invention

[0004] The present invention provides a chicken cartilage-based carbon material. The carbon material is prepared by using chicken cartilage as a raw material. Because the cartilage tissue not only contains a large amount of carbon source, but also naturally contains a certain amount of nitrogen source and a small amount of metal elements, which are retained during the carbonization process, and can improve the electrochemical performance of the carbon material. The use of the raw material to make bio-based carbon materials is not only low-cost, but also pollution-free.

[0005] The method for preparing the chicken cartilage-based carbon material comprises the following steps:

[0006] (1) The chicken cartilage tissue is washed with water and ethanol and then dried to obtain a dry animal cartilage tissue.

[0007] Among them: use ethanol to wash repeatedly for more than three times, and keep it in an oven at 80°C for 24 hours during drying.

[0008] (2) The dried cartilage tissue is placed in a grinder to obtain powder, which is placed in a porcelain cup, placed in a tube furnace for pre-carbonization for 60 minutes, and ground.

[0009] Wherein: the pre-carbonization temperature is 300°C, and the heating rate is 5°C / min.

[0010] (3) The material obtained in step (2) is mixed and soaked with a saturated KOH solution, and dried for later use

[0011] Wherein: the mass ratio of KOH to the material obtained in step (2) is 2:1, and the soaking time is 12 hours.

[0012] (4) After the material obtained in step (3) is carbonized, it is repeatedly washed with distilled water and filtered until it becomes neutral, and then dried for later use to obtain JRG.

[0013] The carbonization temperature is set at 400-600°C, the carbonization time is 120 min, and the heating rate is 10°C / min. The heating rate of carbonization is higher than that of pre-carbonization.

[0014] (5) JRG, aniline (AN), analytical grade sulfuric acid, and ammonium persulfate were mixed and stirred at 8°C for 6 h.

[0015] The mass ratios of AN:JRG:ammonium persulfate are 3-6:1:10 respectively; the dosage ratio of analytical pure sulfuric acid and ammonium persulfate is 80ml:10g.

[0016] (6) The product obtained by the reaction is mixed with an appropriate amount of distilled water, cooled and filtered, washed with distilled water until the pH is neutral, and dried to obtain the product.

[0017] The chicken cartilage-based carbon material is used to make electrodes, which can be used to prepare capacitors.

[0018] Compared with the prior art, the beneficial effects of this application are:

[0019] 1. The present invention uses chicken cartilage tissue as a raw material to prepare carbon materials, realizing high value-added utilization of chicken cartilage, a cheap and abundant resource. In addition, chicken cartilage is rich in organic components such as collagen and chondroitin sulfate, and can form a unique carbon structure during carbonization and activation, which helps to improve the electrochemical performance of carbon materials.

[0020] 2. The present invention prepares carbon materials with special structures and properties through processes such as pre-carbonization, activation, carbonization and composite polyaniline, and optimizes the process. The preparation reaction conditions are relatively mild and the operation is simple, which is an environmentally friendly process route.

[0021] 3. It can be used in the field of electrochemistry. In the electrochemical performance test, it shows higher specific capacitance and faster charging and discharging performance, providing new options for the development of capacitor electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Thermogravimetric diagram of chicken cartilage;

[0023] Figure 2 The constant current charge and discharge diagrams of the electrode sheets of Examples 1, 2, and 3;

[0024] Figure 3 The constant current charge and discharge diagrams of the electrode sheets of Examples 4, 5 and 6, wherein N represents aniline;

[0025] Figure 4 The cyclic voltammograms of the electrode sheets of Examples 4, 5 and 6, wherein N represents aniline;

[0026] Figure 5 Cyclic voltammograms of the electrode sheets of Examples 1, 2 and 3;

[0027] Figure 6 This is a constant current charge and discharge diagram of the electrode sheet of Example 7;

[0028] Figure 7 This is the XPS test image of chicken cartilage, in which the O1s content is 17.68%, the C1s content is 73.48%, and the N1s content is 7.08%;

[0029] Figure 8 This is the electron microscope image of the carbide of Comparative Example 1;

[0030] Fig. 9 This is the electron microscope image of the carbide in Example 1. DETAILED DESCRIPTION

[0031] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any design result and idea of ​​the present invention with simple changes or modifications shall fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0032] The present invention provides a method for preparing a carbon material from chicken cartilage tissue, and the specific steps are as follows:

[0033] First, the appropriate carbonization temperature range was established based on the thermogravimetric test results of cartilage. The collected animal cartilage tissue was washed with distilled water and ethanol and then dried in an 80°C oven for 24 hours. After drying, it was crushed with a grinder for use. A certain amount of chicken cartilage powder was placed in a porcelain cup and placed in a tube furnace. The carbonization temperature was 300°C, the heating rate was 5°C / min, the pre-carbonization was 60 minutes, and the grinding was performed. The activation method was selected as follows: after grinding, it was mixed with a saturated KOH solution and soaked for 12 hours and then dried. The mass ratio of KOH to material was 2:1, and the secondary carbonization was performed. The carbonization temperature was carbonized at 400, 500, 600, and 700°C for 60 minutes. After carbonization, it was repeatedly washed with distilled water until neutral, and after drying, it was stirred at low temperature for 6 hours with a certain amount of aniline (AN), sulfuric acid, and ammonium persulfate.

[0034] The method of the present invention is further described below in conjunction with embodiments, which are not intended to be limiting of the present invention.

[0035] Example 1

[0036] The chicken cartilage collected from the market was washed with distilled water and ethanol and then placed in an 80°C oven for 24 hours. After drying, it was crushed with a grinder for use. Weigh 10g of powder and put it into a tubular furnace. The heating rate was 5°C / min, the carbonization temperature was 300°C, and the carbonization time was 60min. After the tubular furnace was cooled, the sample was taken out and weighed and ground. It was soaked in a saturated KOH solution for 12 hours. The mass ratio of KOH to the material was 2:1. After drying, it was placed in a tubular furnace with nitrogen gas. The heating rate was 10°C / min, the carbonization temperature was 400°C, and the carbonization time was 120min. After the tubular furnace was cooled, it was repeatedly washed with distilled water until the pH was neutral. After drying, JRG was obtained. 1g of sample was mixed with 3g of aniline in 50ml of analytical pure sulfuric acid, stirred until the precipitate was dissolved, and a mixture of 10g of ammonium persulfate and 30ml of analytical pure sulfuric acid was slowly added. The reaction was carried out at 8°C for 6 hours. Wash and dry to obtain chicken cartilage-based carbon material.

[0037] Acetylene black, PVDF and chicken cartilage-based carbon materials were mixed in a mass ratio of 1:1:8 and placed in a grinder. A certain amount of N-methylpyrrolidone was added and ground into a black, bright muddy mixture. After drying to a gelatinous state, the mixture was evenly coated on a 1 cm×2 cm nickel foam; compacted and dried, the sheets were weighed to determine the amount of active substances, and the prepared electrode sheets were used in electrochemical performance tests such as constant current charge and discharge and cyclic voltammetry tests in a three-electrode system.

[0038] The electrochemical properties were measured using a CHI760 electrochemical workstation with a three-electrode system (electrode 1: platinum wire electrode, electrode 2: calomel electrode, working electrode: electrode to be tested). The electrolyte was 3 mol / L KOH, and the capacitance was 132 F / g at a current density of 1 A / g.

[0039] Example 2

[0040] On the basis of Example 1, the second carbonization temperature was set to 500°C, and its electrochemical performance was measured. The capacitance was 189 F / g at a current density of 1 A / g.

[0041] Example 3

[0042] On the basis of Example 1, the second carbonization temperature was 600°C, and its electrochemical performance was measured. When the current density was 1 A / g, the capacitance was 284 F / g.

[0043] Example 4

[0044] The collected chicken cartilage was washed with distilled water and ethanol and then placed in an 80°C oven for 24 hours. After drying, it was crushed with a grinder for later use. Weigh 10g of powder and put it into a tubular furnace. The heating rate was 5°C / min, the carbonization temperature was 300°C, and the carbonization time was 60min. After the tubular furnace was cooled, the sample was taken out, weighed, and ground. It was soaked in a saturated KOH solution for 12 hours. The mass ratio of KOH to material was 2:1. After drying, it was placed in a tubular furnace with nitrogen gas. The heating rate was 10°C / min, the carbonization temperature was 600°C, and the carbonization time was 120min. After the tubular furnace was cooled, it was repeatedly washed with distilled water until the pH was neutral. After drying, 1g of the sample was mixed with 4g of aniline in 50ml of analytical pure sulfuric acid, stirred until the precipitate dissolved, and ammonium persulfate was slowly added dropwise. The reaction was carried out at 8°C for 6 hours. After washing and drying, samples were taken to make electrode sheets, and their electrochemical properties were measured. When the current density was 1A / g, the capacitance was 237.5F / g.

[0045] Example 5

[0046] On the basis of Example 4, the mass of aniline was 5 g, and its electrochemical performance was measured. When the current density was 1 A / g, the capacitance was 305.3 F / g.

[0047] Example 6

[0048] On the basis of Example 4, the mass of aniline was 6 g, and its electrochemical performance was measured. When the current density was 1 A / g, the capacitance was 267 F / g.

[0049] Example 7

[0050] The collected chicken cartilage was washed with distilled water and ethanol and then placed in an 80℃ oven for 24h. After drying, it was crushed with a pulverizer for use. Weigh 10 powders and put them into a tubular furnace. The heating rate was 5℃ / min, the carbonization temperature was 300℃, and the carbonization time was 60min. After the tubular furnace was cooled, the sample was weighed and ground, and soaked in a saturated KOH solution for 12h. The mass ratio of KOH to material was 2:1. After drying, it was placed in a tubular furnace with nitrogen gas, the heating rate was 10℃ / min, the carbonization temperature was 700℃, and the carbonization time was 120min. After the tubular furnace was cooled, it was repeatedly washed with distilled water until the pH was neutral. After drying, 2g of the sample was taken and mixed with 5g of aniline in 50ml of analytical pure sulfuric acid, stirred until the precipitate dissolved, and ammonium persulfate was slowly added dropwise. The reaction was carried out at 8℃ for 6h. Wash and dry, take samples to make electrode sheets, and measure their electrochemical properties. The capacitance was 740F / g at a current density of 0.5A / g.

[0051] Comparative Example 1

[0052] The collected chicken cartilage was washed with distilled water and ethanol and dried in an oven at 80°C for 24 hours. After drying, it was crushed with a grinder for use. Weigh 10 powders and put them into a tubular furnace. The heating rate was 5°C / min, the carbonization temperature was 300°C, and the carbonization time was 60min. After the tubular furnace was cooled, the sample was taken out and weighed, and then it was evenly ground and mixed with twice the mass of KOH solid and placed in a tubular furnace with nitrogen. The heating rate was 10°C / min, the carbonization temperature was 600°C, and the carbonization time was 120min. After the tubular furnace was cooled, it was repeatedly washed with distilled water until the pH was neutral. After drying, 1g of the sample was taken and mixed with 3g of aniline in 50ml of analytical pure sulfuric acid. Stir until the precipitate was dissolved, and slowly drop a mixture of 10g of ammonium persulfate and 30ml of analytical pure sulfuric acid. React at 8°C for 6h. Wash and dry to obtain chicken cartilage-based carbon materials. Make electrode sheets and test their electrochemical properties. At a current density of 1A / g, the capacitance is 38F / g.

[0053] The above description is only a partial specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a chicken cartilage-based carbon material, characterized in that: The steps include: (1) Clean and crush chicken cartilage; (2) Pre-carbonization and then grinding; (3) Alkali leaching; (4) Carbonization and washing; (5) Aniline modification.

2. The method for preparing the chicken cartilage-based carbon material according to claim 1, characterized in that: The pre-carbonization temperature is 300° C., the time is 60 min, and the heating rate is 5° C. / min.

3. The method for preparing the chicken cartilage-based carbon material according to claim 1, characterized in that: The specific steps of alkali leaching are: immersing in alkali solution for 12 hours, filtering, and drying; the alkali solution is a saturated KOH solution, and the mass ratio of KOH to the material obtained in step (2) is 2:

1.

4. The method for preparing the chicken cartilage-based carbon material according to claim 1, characterized in that: The carbonization temperature is 400-600°C, the time is 120 minutes, and the heating rate is 10°C / min.

5. The method for preparing the chicken cartilage-based carbon material according to claim 1, characterized in that: The specific steps of aniline modification are: mixing the material obtained in step (3) with aniline, analytical pure sulfuric acid and ammonium persulfate and stirring for reaction.

6. The method for preparing the chicken cartilage-based carbon material according to claim 5, characterized in that: The mass ratio of the aniline, the material obtained in step (3), and ammonium persulfate is 3-6:1:10; The usage ratio of analytical pure sulfuric acid and ammonium persulfate is 80ml:10g.

7. The method for preparing the chicken cartilage-based carbon material according to claim 5, characterized in that: The stirring reaction temperature is 8°C and the time is 6 hours.

8. A chicken cartilage-based carbon material prepared by the method according to any one of claims 1 to 7.

9. Use of the chicken cartilage-based carbon material according to claim 8 in electrode preparation.